HPK1 kinase inhibitor: a sufficient approach to target HPK1 to modulate T cell activation in cancer immunotherapy compared with degraders - Wang, Qin; Zhu, Xinyi; Li, Jing; Xu, Sanjia; Wang, Ali; Zhang, Xinwen; Wang, Xingxing; Cai, Xiaopeng; Xing, Haimei; Liu, Ye; Liu, Xuesong; Wang, Zhiwei; et al. (Frontiers in Immunology, 2025)
BackgroundHematopoietic progenitor kinase 1 (HPK1) is a member of the mitogen-activated protein kinase kinase kinase kinase (MAP4K) family. It has been reported that HPK1 negatively regulates the activation of T cells. Several compounds have been developed and tested in clinical trials to target HPK1 for cancer immunotherapy. However, whether kinase inhibition is sufficient to eliminate the immunosuppressive function of HPK1, particularly in T cells, remains elusive.MethodsIn this study, genetic tools were used to edit the human T lymphocyte cell line Jurkat. The activation of HPK1-null cells, HPK1-wildtype cells and HPK1-kinase-inactive cells was compared through ectopic expression of HPK1 in HPK1 knockout cells or direct HPK1 mutation. Besides genetic validation, a series of compounds that selectively target HPK1 (with or without HPK1-degradation activity) were used to assess the potential scaffold function of HPK1 in regulation of human primary T cell activation and cytotoxic activity.Results and conclusionAugmented T-cell receptor (TCR)-induced activation in HPK1-knockout Jurkat cells was inhibited by complementation of wildtype, but not kinase-dead HPK1. HPK1 K46E-knockin and K46*-knockin Jurkat cells showed comparable levels of enhanced TCR-induced activation compared with control HPK1-wildtype Jurkat cells. Similarly, HPK1 kinase inhibitor (Compound 1) and cereblon-based (CRBN-based) HPK1 degrader (Compound 2) elicited similar degrees of maximum TCR-induced activation in primary human peripheral blood T cells. In summary, the results of this study suggested that HPK1 kinase inhibitor may be sufficient for HPK1 targeting in T cell mediated cancer immunotherapy.